Identidade institucional e reputação em uma organização privada sem fins lucrativos - Braz, Célia Lucia do Rosario (2013)
The current demands of our society, predicated on the aspects of information economy, culture of service and knowledge society, make the reputation one of the greatest values that an organization can have today, and can be understood as a "vote of confidence" that organization acquired. However, reputation, image and identity are a closely linked phenomena in organizations, to the extent that an identity able to create a good image in the minds of stakeholders can have a positive impact on corporate reputation. At that time, in Brazil, the private nonprofit organizations are not in a comfortable position when it comes to trust in institutions. Thus, the primary objective of this study is to clarify how the institutional identity of a social organization can influence the construction and maintenance of its corporate image and reputation, on the premise that these three concepts are interrelated. To meet this objective, we conducted a case study of qualitative and quantitative approach with the Arco Associação Beneficente, an institution of 22 years that serves children and youth with education services and social assistance. We investigated (i) its institutional identity, composed of the essential attributes of organizational identity and the way these projects are externally - corporate identity, (ii) the general impression that the general public has about the organization - its corporate image, and (iii) evaluation of key stakeholders about the institution - their corporate reputation. Among the results, are: consistency between organizational identity and corporate identity of Arco, except for formal communication factor, a high level of knowledge about the existence of the institution in the region, accompanied by a positive corporate image, and the realization of the strong influence that the institutional identity plays in building and maintaining the reputation of the entity